2018
DOI: 10.1021/acs.nanolett.8b00028
|View full text |Cite|
|
Sign up to set email alerts
|

Ga–Doped Pt–Ni Octahedral Nanoparticles as a Highly Active and Durable Electrocatalyst for Oxygen Reduction Reaction

Abstract: Bimetallic PtNi nanoparticles have been considered as a promising electrocatalyst for oxygen reduction reaction (ORR) in polymer electrolyte membrane fuel cells (PEMFCs) owing to their high catalytic activity. However, under typical fuel cell operating conditions, Ni atoms easily dissolve into the electrolyte, resulting in degradation of the catalyst and the membrane-electrode assembly (MEA). Here, we report gallium-doped PtNi octahedral nanoparticles on a carbon support (Ga-PtNi/C). The Ga-PtNi/C shows high O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
97
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 54 publications
3
97
0
Order By: Relevance
“…Those (111), (200), and (220) peaks are face centered cubic and consistent with the other reported works . The ncs‐Pt showed high‐index facets (200), (210), (211), and (300) compared to other reported works . This consequently leads to higher catalytic activity due to the presence of high‐density atomic steps, ledges, and kinks .…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Those (111), (200), and (220) peaks are face centered cubic and consistent with the other reported works . The ncs‐Pt showed high‐index facets (200), (210), (211), and (300) compared to other reported works . This consequently leads to higher catalytic activity due to the presence of high‐density atomic steps, ledges, and kinks .…”
Section: Resultssupporting
confidence: 89%
“…[31] The ncs-Pt showed high-index facets (200), (210), (211), and (300) compared to other reported works. [10,16,[32][33][34][35] This consequently leads to higher catalytic activity due to the presence of high-density atomic steps, Articles ledges, and kinks. [36] Moreover, at 2θ values of 38.35°and 44.46°t wo diffraction patterns appeared which can be assigned to Au (111) and Au (200), respectively; which probably occurred due to the Au coated substrate.…”
Section: Physical Characterization Of Ncs-ptsmentioning
confidence: 99%
“…100 A recent study by Cho and co-workers compared the morphological and compositional evolutions of Pt−Ni octahedra with and without Ga modification ( Figure 7b). 107 It revealed that the majority of Pt−Ni particles incorporated with <2 at. % of Ga maintained their octahedral shape after 30k cycles, while the Pt−Ni counterparts became spherical after only 4k cycles.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…2020, 120, 1184−1249 maintaining the octahedral shape in a long-term electrochemical measurement. 100,107,112 The addition of Mo has been demonstrated to suppress the dissolution of Ni in acidic media. 113 In Mo-doped Pt 3 Ni octahedra, DFT calculations suggested that there is a strong tendency for Mo to segregate onto vertex sites of octahedra, stabilizing both Ni and Pt atoms through the formation of relatively strong Mo−Pt and Mo−Ni bonds.…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…In addition, the Pt-based catalysts are easily poisoned by the generation of intermediates of carbon monoxide (CO) during the electrooxidation reaction of methanol, which propitiates complete cuts down the electrocatalytic activity and stability of the catalysts [6]. Substantial investigation has been directed toward development of new catalysts via alloying of Pt with other less expensive metals such as Pd, Ag, Au, Cu, etc., either as bimetallic alloys or core–shell architecture in order to reduce the Pt-utlization and, at the same time, to enhance significantly the electrocatalytic activity [7,8,9]. One promising strategy is to design a catalyst comprising of Pt-monolayer onto a less expensive metallic substrates (Pd, Ag, Au, Ir, Co, etc.)…”
Section: Introductionmentioning
confidence: 99%